The personal safety burden for women taking public transport in Australia and implications for provision of equitable public transport - Julie A. King; Dominique A. Greer; Rae S.M. Danvers; Byron W. Keating (Journal of Public Transportation)
Travel on public transport for women is associated with concerns about safety from harassment and violence, and women may avoid public transport or make changes to their travel as a consequence. This qualitative research aimed to explore women’s experiences on public transport, the steps they take to avoid harassment and violence, and what they thought could be done to improve their safety. Women (n = 44) in Australia’s two largest cities, Sydney and Melbourne, were recruited for focus group discussions and their responses were analysed thematically. The results showed that women experience a personal safety burden, due to the need to anticipate possible exposure to harassment and violence, plan ways of avoiding or mitigating the risk, and use defensive tactics to cope with uncomfortable situations. This personal safety burden has five dimensions: cognitive, temporal, emotional, financial and social. The responses showed that women tended to take the public transport system as a given, and to believe they needed to take responsibility for their own safety, so that they did not nominate particular solutions for public transport providers to implement. However, it was evident that the features of public transport travel that participants felt were safer, such as the presence of trained staff, are diminishing with the move to greater use of technology and automation. It is considered that public transport providers have an obligation to ensure that women are not disadvantaged by the personal safety burden observed in this research. It is recommended that public transport providers note the existing features that women find safer (e.g., well-lit environment, presence of trained staff) and seek to extend their provision; and investigate innovative means of maintaining and enhancing safety for women while pursing technological change.